2014
DOI: 10.1136/emermed-2013-203200
|View full text |Cite
|
Sign up to set email alerts
|

A simple tool to predict admission at the time of triage

Abstract: AimTo create and validate a simple clinical score to estimate the probability of admission at the time of triage.MethodsThis was a multicentre, retrospective, cross-sectional study of triage records for all unscheduled adult attendances in North Glasgow over 2 years. Clinical variables that had significant associations with admission on logistic regression were entered into a mixed-effects multiple logistic model. This provided weightings for the score, which was then simplified and tested on a separate valida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
129
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(135 citation statements)
references
References 20 publications
3
129
3
Order By: Relevance
“…[10] Arrival characteristics to the Emergency Department, such as time of arrival, mode of arrival, and triage category, may be useful prognostic factors for outcomes such as probability of admission, length of stay, or mortality. [11] There are few publications regarding ED arrival characteristics of migraine patients.…”
Section: Prevalence and Impactmentioning
confidence: 99%
“…[10] Arrival characteristics to the Emergency Department, such as time of arrival, mode of arrival, and triage category, may be useful prognostic factors for outcomes such as probability of admission, length of stay, or mortality. [11] There are few publications regarding ED arrival characteristics of migraine patients.…”
Section: Prevalence and Impactmentioning
confidence: 99%
“…Also, a system capable of accurately establishing the probabilities of inpatient admission (hospitalization) for every ED patient right after triage can help streamline operations and establish priorities for clinical personnel, bed managers and supporting personnel. Previous research had shown that clinical triage 1 personnel could not predict the need for inpatient admission with sufficient reliability [21][22][23], however, models with a manageable number of easily-obtainable variables and a simple procedure for calculating the probabilities of admission could be used to aid in this task [24][25][26]. In both cases (ED census forecasts and prediction of probabilities of inpatient admission from the ED) predictive models with varying degrees of sophistication can be developed.…”
Section: Glossary Of Terms and Abbreviationsmentioning
confidence: 99%
“…Examples of these are the total number of pharmacy dispensations in primary care [24] for a given patient, or standardized chronic clinical conditions [25], which are not available in all EDs of specialized care hospitals in real time (or at all). Also, several models relied on variables which were highly specific to a country or a region [25,26], which made them impossible to apply in other regional settings.…”
Section: Glossary Of Terms and Abbreviationsmentioning
confidence: 99%
See 2 more Smart Citations